Syntaxonomical approach for classification of the Californian serpentine annual grasslands - Rodriguez-Rojo, Maria del Pilar; Sánchez-Mata, Daniel; Rivas-Martínez, Salvador; Barbour, Michael G. (Lazaroa, 2001)
A preliminary syntaxonomical approach for the serpentine annual grasslands classification is presented. Our proposals include the phytosociological frame for the syntaxonomy of the annual plant communities growing on ultramafic substrata and distributed throughout the territories of the Californian biogeographical region. All the formal phytosociological high units newly proposed are justified and legitimated on the basis of previous reports and our own data. These are collected in a new phytosociological class: Vulpio microstachyos-Hesperolinetea micranthi that includes, so far, one new order: Eriogono luteoli Hesperolinetalia micranthi and four new alliances: Hesperevaco sparsiflorae-Hemizonion congestae, Hesperolinion clevelandii, Hesperolino micranthi-Navarretion filicaulis and Streptanthion polygaloidis.